The future of computing: after the PC. (Economist, 1998)
The writer discusses the future of computing as the personal computer (PC)—the machine that has dominated the 1990s—enters its twilight years by the beginning of the new millennium. He is argues that although users are not about to abandon their PCs altogether, they will find that their computing needs are better catered for by specialized appliances and devices that exploit Internet standards, the Java programming language, and lots of cheap processing power.